Depression and its associated factors among elderly people of old age homes and community of Kathmandu district, Nepal: a comparative study - Mali, Prajita; Poudel, Eak Narayan; Mali, Sushmita; Poudel, Lisasha; Joshi, Santosh Prakash (International Journal Of Community Medicine And Public Health, 2021)
Background: Depression is a common public health problem among elders worldwide and is associated with high morbidity and disability. This study aims to assess depression and its associated factors among elderly in old-age homes and a community of Kathmandu district. Method: A comparative cross-sectional study recruited 122 elderly from old-age homes and a community of Kathmandu district. Depression was measured using the Geriatric Depression Scale-short scale (GDS-15). Socio-demographic and medical history was collected using semi-structured questionnaire. We utilized bivariate logistic regression to assess the association of depression with each variable. Results: The prevalence of depression among elderly in old-age homes was 74.6% and in community was 41.8%. The study found that elderly residing at old age homes were four (OR=4.087; 95% CI=2.373-7.038) times more likely to have depression than those residing in the community. Age was found to be associated with depression among the respondent of both settings. In old-age homes, not receiving old-age allowance, bad perception of life, bad social relation, having a chronic disease, lack of care from family, stress and weeping as stress coping strategy were associated with depression. In the community, stress, non-involvement in family decision making, feeling of neglect, dysfunctional capability, bad social relation, lesser monthly income had positive relation with depression. Conclusion: Depression is highly prevalent among Nepalese elderly, with higher burden in those living in old-age homes. This emphasizes the need for screening of depression among elderly, to initiate early intervention measures.